Use of Combined Hormonal Contraceptives Among Women With Migraines and Risk of Ischemic Stroke. Issue 9 (September 2017) - Champaloux, Steven W.; Tepper, Naomi K.; Monsour, Michael; Curtis, Kathryn M.; Whiteman, Maura K.; Marchbanks, Polly A.; Jamieson, Denise J.
Abstract : (Abstracted from Am J Obstet Gynecol 2017;216:489.e1–489.e7) Migraine headaches occur commonly in women; more than 40% will have a migraine during their lifetime. Women of reproductive age who experience migraine, especially those with aura are at increased risk of ischemic stroke.